Facial Expression Recognition and ReHo Analysis in Major Depressive Disorder - Liu, Sijia; Ma, Ruihua; Luo, Yang; Liu, Panqi; Zhao, Ke; Guo, Hua; Shi, Jing; Yang, Fude; Tan, Yunlong; Tan, Shuping; Wang, Zhiren (Frontiers in Psychology, 2021)
In this study, two of the six facial expressions (happiness, sadness, anger, fear, aversion, and surprise) were presented in quick succession using a short expression recognition test. The differences in facial expression recognition between MDD patients and healthy people were compared. Further, the differences in ReHo values between the two groups were compared using a resting-state functional magnetic resonance imaging (fMRI) scan to investigate the characteristics of spontaneous brain activity in the resting state and its relationship with clinical symptoms and the accuracy of facial expression recognition in patients with MDD. Results 1. The accuracy of facial expression recognition in patients with MDD was lower than that of the HC group. The reaction time for facial expression recognition in the patient group was significantly longer than that of the HC group. 2. Compared with the HC group, the ReHo values decreased in multiple brain regions in the resting state, and there was a dual phenomenon of the increase and decrease of Reho value. 3. Spearman correlation analysis showed no statistical correlation between ReHo and HAMD-17 scores in MDD patients (p>0.05). The changes of spontaneous activity in the left putamen, right angular gyrus and right medial superior frontal gyrus were correlated with the accuracy of facial expression recognition Conclusion In view of the different performance of patients with MDD in facial expression tasks, facial expression recognition may have some suggestive effect on the diagnosis of depression and has clinical guiding significance. Many brain regions, including the frontal lobe, temporal lobe, striatum, hippocampus, and thalamus, in patients with MDD show extensive ReHo abnormalities in the resting state. These brain regions with abnormal spontaneous neural activity are important components of LCSPT and LTC circuits, and their dysfunctional functions cause disorder of emotion regulation. The changes in spontaneous activity in the left putamen, right angular gyrus, and right medial superior frontal gyrus may represent the abnormal pattern of spontaneous brain activity in the neural circuits related to emotion perception and may be the neural basis of facial expression recognition.